Aids answers and breakthoughs (changing faces and ending the epidemic) - Kekoolani, Dean P. ([S.L.] : Vantage Point production (production company) ; Singapore : International Publishers Direct [distributor], 2004)
Discussion about AIDS and the challenging to coping with the personal and emotional issues of the disease
Edited by, Joseph Kleinmen, Sheila O' Callaghan
Narrator: Fred Guernsey
Keywords: AIDS (Disease) -- Prevention; HIV (Viruses)